2021
DOI: 10.1007/978-3-030-73696-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Identification of COVID-19 Related Fake News via Neural Stacking

Abstract: Identification of Fake News plays a prominent role in the ongoing pandemic, impacting multiple aspects of day-to-day life. In this work we present a solution to the shared task titled COVID19 Fake News Detection in English, scoring the 50th place amongst 168 submissions. The solution was within 1.5% of the best performing solution. The proposed solution employs a heterogeneous representation ensemble, adapted for the classification task via an additional neural classification head comprised of multiple hidden … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Although no results were found in the literature for the ISOT dataset used in the article, for similar datasets and similar challenges related to the detecting fake news, the authors in articles [32] and [1] obtained results of a similar range. The COVID-19 dataset, related to the competition under CONSTRAINT 2021 [25] [26], was the subject of research in [13] [22] [16] primarily in the range of f1-score metrics. The best results obtained in this study, in relation to the f1-score, exceed all those reported so far.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although no results were found in the literature for the ISOT dataset used in the article, for similar datasets and similar challenges related to the detecting fake news, the authors in articles [32] and [1] obtained results of a similar range. The COVID-19 dataset, related to the competition under CONSTRAINT 2021 [25] [26], was the subject of research in [13] [22] [16] primarily in the range of f1-score metrics. The best results obtained in this study, in relation to the f1-score, exceed all those reported so far.…”
Section: Resultsmentioning
confidence: 99%
“…Various techniques are used to improve the quality of the metrics. The authors of the article [16], in order to maximize the f1score metric, adopted, among others, a strategy of constructing handcrafted features that captured the statistical distribution of words and characters [16]. In turn, in the work [22] to maximize the metrics, pseudo-label algorithm and text-transformers architecture, consisting of five different Transformers models (BERT, Emie, RoBERTa, XLnet, Electra), were applied [22].…”
Section: Results' Refinementmentioning
confidence: 99%
See 2 more Smart Citations
“…After classification experiments, LR achieved 75.65% accuracy, embedding with dense layer achieved 86.93% accuracy, embedding with LSTM layer achieved 86.9% accuracy, and bi-LSTM model achieved 72.31% accuracy. [52] states in their research that fake news have important role in everyone's life in these days. An individual's life can totally change due to these fake COVID-19 news.…”
Section: Literature Reviewmentioning
confidence: 99%